Impalement injuries of the shoulder: a case report with literature review - Scaglia, Marco; Negri, Stefano; Pellizzari, Gianmarco; Amarossi, Andrea; Pasquetto, Davide; Samaila, Elena Manuela; Maluta, Tommaso; Vecchini, Eugenio; Ricci, Matteo; Valentini, Roberto; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2022)
The management of penetrating skeletal extremity trauma is a clinical challenge even for experienced surgeons. While the treatment of associated vascular injuries should be prioritized, there is still a lack of evidence regarding the management of foreign bodies in case of bone fractures or neurological injuries.Here we present a case of impalement of the right proximal humerus with a construction steel rod. The 54-year-old man was successfully treated without vascular, neurological, and thoracic sequelae.A review of the current literature about the most appropriate extrication sequences and soft tissue reconstruction following massive foreign body injuries was carried out.